"Of Medicineз Sedatyueз": Some Notes on Adjective Position and Oral Register in Middle English Medical Texts - Moskowich, Isabel (Studia Anglica Posnaniensia, 2009)
This paper aims at analysing the word-order patterns of adjectives in the emerging scientific writing in the Middle Ages, particularly in medical texts written in English. To this end, several texts contained in MEMT (Middle English Medical Texts) will be analysed. As a first approach, samples belonging to the three different traditions included in the Corpus will be considered. This examination of samples from a surgical text, a specialised one and a remedy book will also help obtain some conclusions regarding the evolution in the use of the so called French-type adjectives in the language.